6r-1+6=6r

Simple and best practice solution for 6r-1+6=6r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r-1+6=6r equation:


Simplifying
6r + -1 + 6 = 6r

Reorder the terms:
-1 + 6 + 6r = 6r

Combine like terms: -1 + 6 = 5
5 + 6r = 6r

Add '-6r' to each side of the equation.
5 + 6r + -6r = 6r + -6r

Combine like terms: 6r + -6r = 0
5 + 0 = 6r + -6r
5 = 6r + -6r

Combine like terms: 6r + -6r = 0
5 = 0

Solving
5 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 | | 5x^2-16x-340=0 | | 8-w=8 | | h=81.688+2.392*50.1 | | 3(6+5y)= | | a^2-169=0 | | 10x+1=-9 | | 8senx-3=0 | | F(t)=-16t^2+45t+6 | | -8x-8+2x=-2x | | (180-x)+(90-x)=210 | | 3x^2-8x-340=0 | | (n-8)-(2n+2)= | | 15x-4=x-1 | | 3(-2m+5)=-4m+9-m | | 10+0.07(15x)+9=15x | | 3x+8(2x-6)=2+12x | | 10x^2+1000=0 | | 3y-4=4 | | (22x)(x)+8x+840=0 | | 11(7)-3=7(7)+25 | | 4x^2-5=43 | | 0.4x-1.2=0.15+1.8 | | 16+8m-4+2m=22 | | 10x+1000=0 | | 12x+60-28=9-12x | | 3x+8(2+6)=2+12x |

Equations solver categories